Optimization and industrial application of recycled hydrogen desulfurization process in a hydrogenation unit. (1st November 2016) - Liang, Ma; Bingjie, Wang; Yimou, Wang
ABSTRACT: A novel gas-liquid cyclone operated under high-pressure conditions (13.7 MPa) was developed. For optimizing recycled hydrogen desulfurization system, an array of this type of cyclone separators was set in the top of the high-pressure separator and desulfurizing tower. The industrial application results illustrated that the average separation efficiency of the cyclone deliquid device was 85.4%. By adopting the optimized system, a large amount of investment cost was saved and a series of significant improvements were achieved.